The genetic predisposition to bronchopulmonary dysplasia. Issue 3 (June 2016) - Yu, Kun-Hsing; Li, Jingjing; Snyder, Michael; Shaw, Gary M.; O'Brodovich, Hugh M.
Abstract : Purpose of review: Bronchopulmonary dysplasia (BPD) is a prevalent chronic lung disease in premature infants. Twin studies have shown strong heritability underlying this disease; however, the genetic architecture of BPD remains unclear. Recent findings: A number of studies employed different approaches to characterize the genetic aberrations associated with BPD, including candidate gene studies, genome-wide association studies, exome sequencing, integrative omics analysis, and pathway analysis. Candidate gene studies identified a number of genes potentially involved with the development of BPD, but the etiological contribution from each gene is not substantial. Copy number variation studies and three independent genome-wide association studies did not identify genetic variations significantly and consistently associated with BPD. A recent exome-sequencing study pointed to rare variants implicated in the disease. In this review, we summarize these studies' methodology and findings, and suggest future research directions to better understand the genetic underpinnings of this potentially life-long lung disease. Summary: Genetic factors play a significant role in the development of BPD. Recent studies suggested that rare variants in genes participating in lung development pathways could contribute to BPD susceptibility.